Effect of exogenous hydrazine on metabolic process of anammox bacteria. (1st September 2022) - Xiang, Tao; Liang, Hong; Gao, Dawen
Abstract: The effect of N2 H4 (hydrazine) on AnAOB (anaerobic ammonia oxidizing bacteria) metabolic pattern is unknown. Therefore, the main purpose of this paper was to explore the effects of exogenous N2 H4 on the SAA (specific anammox activity), characteristics and metabolic pathway of AnAOB. The results showed that low N2 H4 concentration (1–5 mg/L) continuous dosing can promote SAA. The promoting effect was found to be more obvious within the dosage of 3–5 mg/L N2 H4 . It was also indicated that high N2 H4 concentration dosing (5–10 mg/L) can trigger the self-protection mechanism of AnAOB granular sludge by secreting a large amount of B-PN (binding polymeric protein). Intermittent addition of N2 H4 at low concentration is conducive to the long-term stable operation of anammox process. Exogenous N2 H4 can be directly oxidized by AnAOB to promote the consumption of NO2 − -N and NH4 + -N. In addition, excess electrons can also drive the process of NO3 − -N reduction and NO2 − -N disproportionation. Theoretically, these reaction processes need two and ten extra electrons respectively, which is not easy to occur compared with the anammox process. Graphical abstract: Image 1 Highlights: High N2 H4 concentration triggered excessive secretion of binding polymeric protein. The oxidation of N2 H4 enhanced the nitrite reduction and anammox process. N2 H4 drive the nitrate reduction and nitrite disproportionation process. Low-frequency supplement of N2 H4 was beneficial for anammox stable operation.